Proceso de atención nutricional en paciente femenino de 60 años de edad con sangramiento digestivo alto. - Gonzales Bazante, Beatriz Silvana (2023)
The present work deals with the implementation of a nutritional care process in the case study of a 60 year old female patient with upper gastrointestinal bleeding, where it is proposed to analyze all the data provided in the nutritional assessment, biochemical results and physical assessment of the patient, it is also intended to develop a nutritional strategic plan according to the mentioned pathology and to follow up on their nutritional status. To carry out this clinical case, the four essential steps to implement a nutritional care process are applied, starting with the analysis of the data provided in the nutritional assessment with the results of anthropometric measurements and biochemical tests performed in the laboratory to obtain a current diagnosis of the patient, the elaboration of a nutritional strategic plan according to the pathology present, which in the case study is upper gastrointestinal bleeding, and a continuous follow-up on the nutritional status and improvement of the person. When analyzing the data obtained, she has a body mass index of 33.3 Kg/m2, which shows a body mass index of 33.3 Kg/m2. 3 Kg/m2, which indicates the presence of obesity grade I, in addition the patient presents anemia, a slight infection according to her lymphocytes and a possible renal damage, in view of these findings a nutritional strategic plan was implemented through the daily consumption of a soft gastric diet, low sodium, high in iron, distributed in 5 meal times, detailing the appropriate portion values and amount of grams of each food until reaching the nutritional calculation for the improvement of the patient according to her pathology, a follow-up of 2 months was made to the patient to observe her progress during the intervention of the nutritional strategic plan, , so it is recommended to the patient to continue with the nutritional strategic plan to improve her health status and lifestyle in a longer period of time.